1999
DOI: 10.1210/endo.140.11.7122
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of the Homeodomain Protein IDX-1 in Mice Transgenic for an IDX-1 Promoter/lacZ Transcriptional Reporter1

Abstract: Expression of the homeodomain transcription factor IDX-1 (also known as IPF-1, STF-1, and PDX-1) is required for pancreas development, because disruption of the gene in mice and humans results in pancreatic agenesis. During embryonic development the idx-1 gene is first expressed in a localized region of foregut endoderm from which the duodenum and pancreas later develop. To more fully understand the role of IDX-1 in pancreas development, transgenic mice expressing the Escherichia coli lacZ gene under control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The transcription factor (TF) Pdx1 plays essential roles in pancreatic tissue development and differentiation of pancreatic cell lineages ( 14 ). In adult mice, Pdx1 is expressed only in specific cell types, such as acinar cells, β cells of the islets, and ductal cells ( 15 17 ). To examine the specificity of Pdx1-Cre–mediated miR-29a depletion in our murine model, we measured miR-29a levels in acinar cells, islets, and PSCs in the mouse pancreata.…”
Section: Resultsmentioning
confidence: 99%
“…The transcription factor (TF) Pdx1 plays essential roles in pancreatic tissue development and differentiation of pancreatic cell lineages ( 14 ). In adult mice, Pdx1 is expressed only in specific cell types, such as acinar cells, β cells of the islets, and ductal cells ( 15 17 ). To examine the specificity of Pdx1-Cre–mediated miR-29a depletion in our murine model, we measured miR-29a levels in acinar cells, islets, and PSCs in the mouse pancreata.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Interestingly, among genes most affected by differential methylation, we identified the pan-stomach developmental regulator GATA Binding Protein 4 (GATA4), Pancreatic And Duodenal Homeobox 1 (PDX1), which is a transcription factor essential for the development of the pancreas and gastroduodenal junction and expressed in gastric antrum (Holland et al, 2013;Offield et al, 1996;Stoffers et al, 1999), as well as Iroquois Homeobox 2 and 5 (IRX2 and IRX5), which have been implicated in the specification of stomach fundus in mice (McCracken et al, 2017) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, its expression is low in some ductal and acinar cells [ 58 , 59 ]. Stoffers et al found that PDX-1 played an important role in developing the exocrine and endocrine portions of the pancreas, pancreatic ducts, pyloric glands of the distal stomach, common bile and cystic ducts, the intestinal epithelium of the duodenum, Brunner’s glands, and the spleen [ 60 ]. In addition to the gastrointestinal system, PDX-1 is expressed in embryonic brain cells during the active nervous system generation phase [ 61 ].…”
Section: Gene Structure and Location Protein Molecular Structure Dist...mentioning
confidence: 99%